PERAN DINAS PERHUBUNGAN KOTA MAKASSAR DALAM UPAYA PENGAWASAN PARKIR LIAR PERSPEKTIF SIYASAH SYAR'IYYAH - Ika Kurnia Purnama, (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This study analyzes parking problems in Makassar City and the government's efforts to overcome traffic jams and illegal parking. Makassar City faces challenges in providing adequate parking space due to rapid population growth and high urbanization. The problems studied include lack of parking space, high land prices, increased vehicle volume, undisciplined behavior of road users, and ineffective implementation of parking regulations. This research also describes the impact of illegal parking such as congestion, energy waste, air pollution, and public inconvenience. Parking is when the vehicle does not move for a while and is abandoned by the driver. According to Sukanto, parking is stopping and storing vehicles (cars, motorcycles, bicycles, etc.) temporarily in a certain space. The space can be in the form of a roadside, garage or yard provided to accommodate the vehicle. This study aims to find out how illegal parking is controlled by the Makassar City Transportation Service and how Siyasah Syar'iyyah views illegal parking supervision. This research is classified as field research with an empirical juridical and normative syar'i approach. The results of this study indicate that the form of control carried out by the Makassar City Transportation Service on several roads is by taking action in accordance with Perwali Number 64 of 2011, such as locking and checking parking permits by business actors. The obstacles faced are the lack of awareness of illegal parking attendants and parking users who park their vehicles in places where parking is prohibited, weak coordination between the Department of Transportation and the PD. Makassar City Parking, as well as other stakeholders. Siyasah Syar'iyyah's view of the Role of the Makassar City Transportation Service in Illegal Parking Control Efforts, that in a hadith narrated by the Muslim Prophet sallallaahu alaihi wasallam narrates: “I saw a man who gets pleasure in heaven because of a tree he cut down on the road because it would interfere with others." shows how noble the Muslims are who practice the demands of Shari'a and Islamic teachings. They have to keep the streets clean, instead of polluting and destroying them. They are encouraged to remove roadblocks or thorns if they come across. This is how the morals of Muslims are taught by Allah's religion while hoping for His reward and pleasure. Therefore, it is hoped that the Makassar City Transportation Service can work together in supervising illegal parking and the intensity of supervision that needs to be increased and also provide strict sanctions to those who violate it, to the parking user community. expected to increase awareness to be more obedient to traffic rules.